Dynamic pricing and market segmentation responses to low-cost carrier entry. (February 2017) - Varella, Rafael R.; Frazão, Jessica; Oliveira, Alessandro V.M.
Highlights: This paper develops an empirical model of online airfare determinants. We inspect if competition with LCC induces major carriers to respond in pricing and distribution. We utilize a database of airfares collected from the website of an online travel agent in Brazil. We test whether incumbents reshape their airfare temporal profiles. Our results suggest that LCC entry partially spoils the existing market segmentation schemes. Abstract: This paper develops an empirical model of online airfares to inspect the impact of the entry of a low-cost carrier (LCC). We utilize a database collected from the website of an online travel agent in Brazil. We test whether incumbents reshape their airfare temporal profiles in an attempt to attract the price-sensitive passengers who constitute the target market of the newcomer. Our results suggest that LCC entry partially spoils the existing market segmentation schemes of incumbents, forcing them to revise their distribution management strategy, simplify their fare structure and migrate from a non-monotonic to a weakly monotonic price curve.